CD142 plays an important role in the mobility of colorectal cancer cells. Issue 9 (1st September 2020) - Gao, Qin; Chen, Zhongbiao; He, Yang; Hou, Zhibin; Ye, Ruifeng; Xue, Wanlin; Lin, Jiahui; Tu, Xiaohuang
ABSTRACT: CD142 promotes cell mobility, which contributes to carcinogenesis. However, the role of CD142 on colorectal cancer (CRC) mobility is unclear. This study showed that CD142 expression increased in CRC tissues, especially in those with invasion or metastasis. The positive sorting or overexpression of CD142 promoted the invasion and migration of CRC cells. Overall, CD142 may be responsible for CRC mobility.